Impact of Ad Libitum Hydration on Muscle and Liver Damage and Electrolyte Balance in Ultra-Trail Events: A Heatmap Analysis of Biomarkers and Event Characteristics—A Pilot Study - Alejandro García-Giménez; Francisco Pradas; Miguel Lecina; Nicolae Ochiana; Carlos Castellar-Otín (Biology)
Ultra-trail events (UTs) pose significant challenges to maintaining hydration and electrolyte balance, with risks of dehydration (DH), overhydration (OH), exercise-associated hyponatremia (EAH), and exertional rhabdomyolysis (ER). This study examined the effects of ad libitum (ADL) hydration on hydration status and muscle damage during a nine-stage UT (635 km, 40,586 m elevation gain). Four highly trained male athletes participated. Hydration was assessed via body weight loss (BWL), urine specific gravity (Usg), and serum sodium ([Na+]), while muscle damage markers included creatine kinase (CK), lactate dehydrogenase (LDH), and calcium (Ca), and liver damage biomarkers included aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Our results showed no cases of EAH or hypernatremia ([Na+] > 145 mmol·L−1), with serum [Na+] maintained above 135 mmol·L−1. BWL exceeded the 2% DH threshold in early stages (p = 0.029), and Usg remained elevated (>1.020 g·mL−1). LDH and CK significantly increased at all stages (p < 0.05), persisting for 48 h post-event. Correlations showed BWL aggravated muscle damage (r = 0.47 with CK) and hypocalcemia (r = −0.68 with Ca). Elevation gain/loss amplified fluid loss and muscle injury. While ADL hydration mitigated EAH, it did not fully address DH or muscle damage. Personalized hydration and recovery protocols are crucial to optimizing performance and health in UT events.